Correlation between Complication in Pregnancy and Postpartum Depression: Literature Review - Desy Meldawati; Fazraningtyas, Winda Ayu; Budi, Setia (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2021)
Postpartum depression is a depression syndrome that occurs in mothers after childbirth and can be prevented and cured. According to Fazraningtyas, in South Kalimantan, to be precise in the city of Banjarmasin, namely Ulin General Hospital of Banjarmasin and Dr. H.M. Ansari Saleh General Hospital of Banjarmasin showed 56.8% mild postpartum depression, 26.1% moderate postpartum depression, 17.0% severe postpartum depression. The impact of mothers experiencing postpartum depression is that mothers have difficulty interacting and can endanger their children. Postpartum depression is caused by several factors, the factors that contributed are complications in pregnancy. This study used a literature review approach. The articles obtained from Google Scholar, Biomed Central, and Pubmed. The criterias applied be restricted. As many as 10 journals are found. Based on the previous study, complications in pregnancy are the cause of postpartum depression. Complications that are often experienced by pregnant women are maternal anemia that can appear during the pregnancy process until the birth process occurs and 30-70% of pregnant women with maternal anemia have a risk of postpartum depression. Second, gestational diabetes is one of the complications of pregnancy that occurs in women who are pregnant. Pregnant women can increase hormones including the progesterone hormone, human placental lactogen estrogen, and cortisol. The last, a history of depression is a cause of postpartum depression because if pregnant women have a history of depression before pregnancy, they will have a higher risk of experiencing postpartum depression.